2017
DOI: 10.1177/1010428317705761
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-34a inhibits tumor invasion and metastasis in osteosarcoma partly by effecting C-IAP2 and Bcl-2

Abstract: Osteosarcoma is a common primary malignant bone tumor that occurs mainly in children and adolescents. Recent evidence has demonstrated that miR-34a is involved in the invasion and metastasis of osteosarcoma. This study aims to explore the effect of biological behavior of miR-34a on osteosarcoma. First, we collect osteosarcoma and adjacent specimens, and the relative expression of miR-34a and C-IAP2 messenger RNA was quantitated by real-time polymerase chain reaction. Furthermore, miR-34a stimulant is synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
(42 reference statements)
3
17
0
Order By: Relevance
“…In addition, miR-34a was regarded as a novel prognostic biomarker and correlated with tumor size and stage in OS ( 45 ). The present study reported that miR-34a was downregulated in OS tissues and cells, in accordance with previous studies ( 24 , 25 ). Additionally, MALAT1 was negatively correlated with miR-34a expression in OS cells.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In addition, miR-34a was regarded as a novel prognostic biomarker and correlated with tumor size and stage in OS ( 45 ). The present study reported that miR-34a was downregulated in OS tissues and cells, in accordance with previous studies ( 24 , 25 ). Additionally, MALAT1 was negatively correlated with miR-34a expression in OS cells.…”
Section: Discussionsupporting
confidence: 94%
“…Recently, increasing evidence has demonstrated that lncRNAs could function as competing endogenous RNAs (ceRNAs) to suppress the expression and activities of miRNAs, thus regulating the expression of target mRNA ( 21 - 23 ). As a well-studied miRNA, miR-34a, a member of the miR-34 family, has been reported as downregulated in OS cells and functioned as a tumor suppressor in the pathogenesis of OS ( 24 , 25 ). Considering the importance of MALAT1 and miR-34a in the pathogenesis of OS, the present study investigated whether MALAT1 functions as a molecular sponge of miR-34a in OS.…”
Section: Introductionmentioning
confidence: 99%
“…BCL-2 acted as an apoptosis factor and was proven to take part in regulating some cancers targeted by miR-34a. It was reported by Wen et al that miR-34a inhibited osteosarcoma cell invasion and migration via targeting BCL-2 and C-IAP2 ( 32 ), which is similar to the study that miR-34a suppressed the viability and migration of breast cancer by inhibiting BCL-2 ( 33 ). Wang et al showed that miR-34a mimic curbed cell viability and facilitated the apoptosis of cervical cancer cell through targeting BCL-2 ( 15 ).…”
Section: Discussionsupporting
confidence: 85%
“…miRNA regulates the important pathophysiological processes in the development, progression, metastasis and chemotherapy of osteosarcoma, providing new ideas for targeted therapy of osteosarcoma [12]. miR-34a-5p [13] and miR-20a-5p [14] can increase the chemosensitivity of osteosarcoma cells; miR-34a inhibits tumor invasion and metastasis of osteosarcoma by affecting C-IAP2 and Bcl-2 [15]. In addition, miR-34a can also reduce the self-renewal ability, tumorigenic activity and invasive ability of cancer stem cells [16].…”
Section: Discussionmentioning
confidence: 99%